2013
DOI: 10.1249/mss.0b013e318271689e
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity, Fitness, and Race

Abstract: Race, PA, and exercise intensity are important factors in explaining differences in CRF. After accounting for demographics, PA, and VMET, a large proportion of the variance in CRF remains unexplained. Thus, other factors should also be considered when examining racial/ethnic differences in CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…Population-based studies have documented racial differences in aerobic capacity among non-Hispanic Black and non-Hispanic White subjects [5][6][7]32]. The largest assessment of aerobic capacity (conducted annually since 1999) is derived from the NHANES, which utilizes a submaximal treadmill exercise test to assess aerobic capacity in healthy adults aged 20-49 years.…”
Section: Evidence Of Racial Differences In Cardiorespiratory Fitnessmentioning
confidence: 99%
“…Population-based studies have documented racial differences in aerobic capacity among non-Hispanic Black and non-Hispanic White subjects [5][6][7]32]. The largest assessment of aerobic capacity (conducted annually since 1999) is derived from the NHANES, which utilizes a submaximal treadmill exercise test to assess aerobic capacity in healthy adults aged 20-49 years.…”
Section: Evidence Of Racial Differences In Cardiorespiratory Fitnessmentioning
confidence: 99%
“…[37][38][39][40] At baseline, participants with SCT in the CARDIA study had a slightly, but significantly, higher diastolic blood pressure compared with those without SCT. However, the absolute difference was small, and the baseline prevalence of hypertension was not higher among participants with SCT.…”
Section: Discussionmentioning
confidence: 96%
“…7 Data from largescale observational studies, including the National Health and Nutrition Examination Survey and Health, Risk Factors, Exercise Training and Genetics studies, have demonstrated lower fitness, measured directly by maximal tests or estimated from submaximal tests, in African American individuals when compared with their Caucasian counterparts. 36,37 However, it is more likely that lower levels of physical activity and higher BMI, which may affect muscle oxidative potential, contribute to disparities in fitness between African Americans and Caucasians. [37][38][39][40] At baseline, participants with SCT in the CARDIA study had a slightly, but significantly, higher diastolic blood pressure compared with those without SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects identified as Caucasian/White, and only one identified as Hispanic/Latino; race of subjects was a known delimitation among our convenience sample. Research suggests that race may substantially influence VO 2max (Ceaser, Fitzhugh, Thompson, & Bassett, 2013 Findings may be limited by the periodical timing of the study. This intervention was implemented during the subjects' offseason and into the beginning weeks of preseason.…”
Section: Limitationsmentioning
confidence: 99%